2014
DOI: 10.1002/ca.22483
|View full text |Cite
|
Sign up to set email alerts
|

Clinical structural anatomy of the inferior pyramidal space reconstructed from the living heart: Three‐dimensional visualization using multidetector‐row computed tomography

Abstract: The inferior pyramidal space (IPS) comprises the epicardial visceral adipose tissue wedged between the bottoms of the four cardiac chambers from the postero-inferior epicardial surface of the heart. Understanding the complex anatomy around the IPS is important for clinical cardiologists. Although leading anatomists and radiologists have clarified the anatomy of the IPS in detail, few studies have demonstrated this anatomy in three dimensions. The aim of this study was to visualize the three-dimensional anatomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…4,25,26 Use of multidetector-row computed tomographic dissection has now served convincingly to endorse the recommendations of the working group. 4, 27 The technique, furthermore, has shown that it is only the atrioventricular component of the membranous septum that is truly septal (Figure 4, Left panel).…”
Section: Acquisition Of Images and Reconstruction For Cardiac Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…4,25,26 Use of multidetector-row computed tomographic dissection has now served convincingly to endorse the recommendations of the working group. 4, 27 The technique, furthermore, has shown that it is only the atrioventricular component of the membranous septum that is truly septal (Figure 4, Left panel).…”
Section: Acquisition Of Images and Reconstruction For Cardiac Anatomymentioning
confidence: 99%
“…Although each image used in the presented figures could have been prepared by any clinician with patience and dedication, it is a team approach, involving cardiac radiologists and technologists that produces optimal results. 27 …”
Section: Revisiting the Anatomy Of The Heart Using Computed Tomographymentioning
confidence: 99%
“…As demonstrated in the present case, MDCT is optimal for obtaining detailed knowledge of the three‐dimensional cardiac structural anatomy of the living heart, including the coronary venous system. Modern MDCT has superior spatial resolution than cardiac magnetic resonance imaging has and therefore enables clear visualization of the branches of coronary venous systems in relation to the cardiac contour (Figure ).…”
Section: Discussionmentioning
confidence: 83%
“…Every study using MDCT requires justification because the procedure is not free from radiation exposure or contrast material. To obtain the best images with minimum radiation exposure and contrast volume, collaboration with cardiac radiologists and radiological technologists is crucial . Therefore, in selected CRT‐D candidates, such as patients with suspected significant anatomical abnormality, patients who undergo coronary arterial evaluation using MDCT, patients with initial procedural failure, and patients with other indication for contrast‐enhanced MDCT, preprocedural MDCT evaluation of the coronary venous system would be an optimal option, combined with an appropriate imaging reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the human heart, this is the inferior pyramidal space (Fig. —Sánchez‐Quintana et al, ; Mori et al, ). In the bovine heart, as already emphasized, the space is much shorter, and less pyramidal (Fig.…”
Section: Resultsmentioning
confidence: 99%